ASFV Gene A151R Is Involved in the Process of Virulence in Domestic Swine - Elizabeth Ramirez-Medina; Elizabeth Vuono; Sarah Pruitt; Ayushi Rai; Nallely Espinoza; Alyssa Valladares; Edward Spinard; Ediane Silva; Lauro Velazquez-Salinas; Douglas P. Gladue; Manuel V. Borca (Viruses, 2022)
African swine fever virus (ASFV) is the etiological agent of a swine pandemic affecting a large geographical area extending from Central Europe to Asia. The viral disease was also recently identified in the Dominican Republic and Haiti. ASFV is a structurally complex virus with a large dsDNA genome that encodes for more than 150 genes. Most of these genes have not been experimentally characterized. One of these genes, A151R, encodes for a nonstructural protein and has been reported to be required for the replication of a Vero-cell-adapted ASFV strain. Here, we evaluated the role of the A151R gene in the context of the highly virulent field isolate Georgia 2010 (ASFV-G) during virus replication in swine macrophage cell cultures and during experimental infection in swine. We show that the recombinant virus ASFV-G-∆A151R, harboring a deletion of the A151R gene, replicated in swine macrophage cultures as efficiently as the parental virus ASFV-G, indicating that the A151R gene is not required for ASFV replication in swine macrophages. Interestingly, experimental infection of domestic pigs demonstrated that ASFV-G-∆A151R had a decreased replication rate and produced a drastic reduction in virus virulence. Animals were intramuscularly inoculated with 102 HAD50 of ASFV-G-∆A151R and compared with pigs receiving a similar dose of virulent ASFV-G. All ASFV-G-infected pigs developed an acute lethal form of the disease, while those inoculated with ASFV-G-∆A151R remained healthy during the 28-day observational period, with the exception of only one showing a protracted, but fatal, form of the disease. All ASFV-G-∆A151R surviving animals presented protracted viremias with lower virus titers than those detected in ASFV-G-infected animals. In addition, three out of the four animals surviving the infection with ASFV-G-∆A151R were protected against the challenge with the virulent parental virus ASFV-G. This is the first report indicating that the ASFV A151R gene is involved in virus virulence in domestic swine, suggesting that its deletion may be used to increase the safety profile of currently experimental vaccines.